Bill 23: Monitoring, standardizing and punishing - Potvin, Maryse; Bilodeau, Simon (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
The passage of Bill 23 aims to improve academic success and excellence in education. However, it is part of a legislative continuum which has led to a growing surveillance and control of the Quebec education system in the hands of the minister of education. This centralization opens the door to ideological management which undermines the education of young people, the training and work of school staff, science, and academic freedom. Borrowing the idea of the panopticon from Foucault, and from James C. Scott’s analysis of the eye of the state, this article presents the risks of authoritarian control with the aim of modernizing, monitoring, standardizing, and punishing.